The presence of depressive symptoms and cognitive performance among older individuals with and without self-reported chronic diseases - Thaís Bento Lima da Silva; Tiago Nascimento Ordonez; Guilherme Alves da Silva; Maria Antônia Antunes de Souza; Sabrina Aparecida da Silva; Gabriela dos Santos; Beatriz Aparecida Ozello Gutierrez; Ana Paula Bagli Moreira; Laydiane Alves Costa; Luiz Carlos de Moraes; Patrícia Prata Lessa; Neide Pereira Cardoso; et al. (Dementia & Neuropsychologia, 2023)
ABSTRACT. Dementias secondary to cardiovascular diseases are the second cause of neurogenerative diseases. These conditions can be prevented by controlling risk factors, and it is necessary to observe the relationship between chronic diseases. Objective: to know the influence of chronic non-communicable diseases on cognition and depressive symptoms in the elderly, amid the COVID-19 pandemic. Methods: 578 older adults were evaluated using a sociodemographic questionnaire, the Brazilian Telephone version of the Mini Mental State Examination (Braztel-MMSE), the Geriatric Depression Scale (GDS-15) and an open questionnaire related to NCDs. Results: the association of Non-Communicable Diseases (NCD) with age, depressive symptoms and schooling was confirmed. Conclusion: no association with cognitive decline was evident due to the relationship of high schooling of participants and control of NCDs.